EMERGENCE AND EVOLUTION OF CIVIL RIGHTS MOVEMENT IN INDIA: AN OVERVIEW - Roy, Soumen (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Usually, civil rights are essential rights to live a peaceful civilized and dignified social life. All civil rights are also identified as important social rights of citizens. In India, the term civil rights, right to individual liberty, human right etc. are used almost synonymously. Civil rights movements in India have a long history. Civil rights movement in India started from the pre-independence period and even in independent India the civil rights movement has gone through various phases and events. The issue of civil rights movement is closely associated with the democratic rights movement, the human rights movement and the national freedom movement. The civil rights movement in India has also started with the national freedom movement during the colonial period. The efforts to protect civil rights that can be traced through India's national liberation movement from the pre-independence era are considered equally relevant long after independence.